2009
DOI: 10.1007/978-3-642-03829-7_4
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Voting in the Netherlands: From Early Adoption to Early Abolishment

Abstract: Abstract. This paper discusses how electronic voting was implemented in practice in the Netherlands, which choices were made and how electronic voting was finally abolished. This history is presented in the context of the requirements of the election process, as well as the technical options that are available to increase the reliability and security of electronic voting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 20 publications
0
16
0
2
Order By: Relevance
“…Whether it is in the long term interest of the operators (and the utility sector at large) remains to be seen. When people are forced to trust a single party, this trust may suddenly collapse, like for voting machines [JP09]. Abuse will get media attention and the premiss of universal trust in the operator will then be questioned.…”
Section: Centralised Trustmentioning
confidence: 99%
“…Whether it is in the long term interest of the operators (and the utility sector at large) remains to be seen. When people are forced to trust a single party, this trust may suddenly collapse, like for voting machines [JP09]. Abuse will get media attention and the premiss of universal trust in the operator will then be questioned.…”
Section: Centralised Trustmentioning
confidence: 99%
“…The original system was designed by Logica CMG and a fully open-source version was later developed [31,32]. Analysis of the main feedback from this experiment was that risk and trust were significant concerns for the public [27] The Rijnland Internet Election System (RIES) system replaced KOA in a follow-up experiment, but many security issues were identified [29]. Subsequently, after an NGO-We Dont Trust Voting Computers-demonstrated that the machine's software could be replaced with a manipulated version within 1 min [19]), the Netherlands stopped the development of their Internet voting project RIES as well as the use of their electronic voting machines.…”
Section: E-voting On-line: the Present Status Around The Worldmentioning
confidence: 99%
“…An example of different approaches to deployment of a new technology is the introduction of electronic voting in the UK and the Netherlands [19,31,36]. In the Netherlands, the decision on whether to adopt electronic voting machines was made by the local authorities.…”
Section: Electronic Votingmentioning
confidence: 99%